Nurses’ Knowledge and Practices Regarding Malnutrition in Children and Its Management - Rashid, Anjum; Arshad, Rabia (Biological and Clinical Sciences Research Journal, 2025)
Malnutrition remains a significant contributor to childhood morbidity and mortality, especially in low- and middle-income countries like Pakistan. Nurses play a vital role in the early identification and management of pediatric malnutrition. Objective: To assess nurses’ knowledge and clinical practices regarding malnutrition in children and its management at a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 150 registered female nurses selected through convenience sampling. Data were collected using a structured, pre-tested questionnaire assessing demographic characteristics, knowledge, and practices related to pediatric malnutrition. Descriptive statistics were analyzed using SPSS version 25, and results were categorized into low, average, and high levels of knowledge and practice. Results: Among the participants, 37.3% demonstrated high knowledge, 35.3% average, and 27.3% low knowledge regarding pediatric malnutrition. However, only 32.7% exhibited average practices, while the majority (67.3%) demonstrated low practice scores. While most nurses correctly identified key concepts related to malnutrition, a significant gap was noted between knowledge and its practical application in clinical care. Conclusion: Although many nurses possessed satisfactory theoretical knowledge of malnutrition, the overall practice levels were suboptimal. This highlights the urgent need for continuous professional development and structured training programs focused on the practical management of malnutrition in pediatric settings.